2019
DOI: 10.1111/ejss.12787
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the variation in organic carbon stocks in agricultural soils of Germany

Abstract: This study gives an overview of soil organic carbon (SOC) stocks in Germany's agricultural soils, and quantifies and explains the influence of explanatory variables such as land use and management, soil type and climate. Over 2500 agricultural sites were sampled and their SOC stocks determined, together with other soil properties. Machine‐learning algorithms were used to identify the most important variables. Land use, land‐use history, clay content and electrical conductivity were the main predictors in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 42 publications
(67 reference statements)
5
54
1
Order By: Relevance
“…Using this method, for example, Hobley et al 2015found climate variables to be key for explaining soil organic C storage in Eastern Australia. Also, in southeast Germany, Wiesmeier et al (2012) identified precipitation and temperature to be important for explaining soil organic C. However, for whole Germany, our study and Vos et al (2019) found climate to be insignificant for explaining soil organic C. Such seemingly contrasting findings can be confusing -they illustrate three major shortcomings of Random Forests in explaining soil organic C: & In contrast to mechanistic models, Random Forest models can only describe patterns within the predictor space they were trained on (Meyer & Pebesma 2020). Random Forest models that are trained to predict organic C in mineral soil (as in this study) will fail to predict organic C in organic soil because, per definition, the organic C content in organic soil is much higher than in mineral soil.…”
Section: Limits Of Random Forest Algorithms In Explaining Soil Organic Ccontrasting
confidence: 53%
See 1 more Smart Citation
“…Using this method, for example, Hobley et al 2015found climate variables to be key for explaining soil organic C storage in Eastern Australia. Also, in southeast Germany, Wiesmeier et al (2012) identified precipitation and temperature to be important for explaining soil organic C. However, for whole Germany, our study and Vos et al (2019) found climate to be insignificant for explaining soil organic C. Such seemingly contrasting findings can be confusing -they illustrate three major shortcomings of Random Forests in explaining soil organic C: & In contrast to mechanistic models, Random Forest models can only describe patterns within the predictor space they were trained on (Meyer & Pebesma 2020). Random Forest models that are trained to predict organic C in mineral soil (as in this study) will fail to predict organic C in organic soil because, per definition, the organic C content in organic soil is much higher than in mineral soil.…”
Section: Limits Of Random Forest Algorithms In Explaining Soil Organic Ccontrasting
confidence: 53%
“…Sorption of organic C on clay surfaces decreases C turnover (von Luetzow et al 2008), whereas microbes allocated on mineral surfaces directly incorporate metabolised C into their biomass and necromass (Kögel-Knabner and Amelung 2014). This makes soil texture a key variable for explaining the C stocks of agricultural soils in Germany (Vos et al 2019).…”
Section: Effects Of Texture and Groundwater On Organic Cmentioning
confidence: 99%
“…Consistent with previous studies, we concluded that organic C is mainly combined with silt and clay in sediment. We found a positive correlation between organic C and clay and a negative relationship between organic C and sand (Vos et al., 2019). Previous studies have found that organic matter can be combined with finer soil particles into an organic–inorganic complex, or agglomerate, which increases the chemical binding capacity and chemical stability of the organic material, reduces the mineralization loss of the organic material, and enriches the organic material of soil particles (Koiter et al., 2017; Wang et al., 2019; Zhen, Ping, Ming, & Jun, 2005).…”
Section: Discussionmentioning
confidence: 53%
“…The ratio of performance to deviation (RPD), i.e., the ratio between the standard deviation and the root mean square error (RMSE), was used as a measure for the estimation accuracy. Additionally, 78 samples of the GASI+Demmin dataset were collected in the framework of the German Agricultural Soil Inventory [21]. These samples were collected from a soil profile in cropland sites at 0-10 cm depth using three 200 cm 3 soil cores.…”
Section: Soc Calibration Models Validation and Mappingmentioning
confidence: 99%